2019
DOI: 10.1007/s00340-019-7326-5
|View full text |Cite|
|
Sign up to set email alerts
|

Electro-optic sensor for static fields

Abstract: A sensor has been developed for low frequency and DC electric fields E. The device is capable of measuring fields with E = 4 (1) V/cm resolution. It is based on a Y-cut Z-propagation lithium niobate electro-optic crystal. For a particular commercially available bare crystal, we achieved an in air time constant c (air) = 6.4(1.8) h for the decay of the electro-optic signal. This enables field monitoring for several hours. As an application, we demonstrated that a constant electric field E ext = 640 V/cm applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Measurements of DC fields have been performed for decades [93,111,149], but mostly no clear estimation of long-term stability was done. Commercial devices that can measure DC fields in a dedicated way do not exist until today [108]. One reason for the difficulties in measuring DC fields are the dielectric relaxation effects in the electro-optical crystal found by Garzarella et al [150].…”
Section: Measurement Systems For Ac Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of DC fields have been performed for decades [93,111,149], but mostly no clear estimation of long-term stability was done. Commercial devices that can measure DC fields in a dedicated way do not exist until today [108]. One reason for the difficulties in measuring DC fields are the dielectric relaxation effects in the electro-optical crystal found by Garzarella et al [150].…”
Section: Measurement Systems For Ac Fieldsmentioning
confidence: 99%
“…One reason for the difficulties in measuring DC fields are the dielectric relaxation effects in the electro-optical crystal found by Garzarella et al [150]. Grasdijk et al [108] demonstrated that the relaxation process can extend from a scale of seconds to hours by minimizing the crystal's temperature dependence using LN (Y-Cut). However, the authors also emphasized that temperature stabilization (∆T < 0.2 K) is essential for long-term DC measurements.…”
Section: Measurement Systems For Ac Fieldsmentioning
confidence: 99%
See 1 more Smart Citation